A Potential Role for Human UDP-Glucuronosyltransferase 1A4 Promoter Single Nucleotide Polymorphisms in the Pharmacogenomics of Tamoxifen and Its Derivatives - Greer, Aleksandra K. (The American Society for Pharmacology and Experimental Therapeutics, 2014)
Tamoxifen (Tam) is a selective estrogen receptor modulator used to inhibit breast tumor growth. Tam can be directly N-glucuronidated via the tertiary amine group or O-glucuronidated after cytochrome P450–mediated hydroxylation. In this study, the glucuronidation of Tam and its hydroxylated and/or chlorinated derivatives [4-hydroxytamoxifen (4OHTam), toremifene (Tor), and 4-hydroxytoremifene (4OHTor)] was examined using recombinant human UDP-glucuronosyltransferases (UGTs) from the 1A subfamily and human hepatic microsomes. Recombinant UGT1A4 catalyzed the formation of N-glucuronides of Tam and its derivatives and was the most active UGT enzyme toward these compounds. Therefore, it was hypothesized that single nucleotide polymorphisms (SNPs) in the promoter region of UGT1A4 have the ability to significantly decrease the glucuronidation rates of Tam metabolites in the human liver. In vitro activity of 64 genotyped human liver microsomes was used to determine the association between the UGT1A4 promoter and coding region SNPs and the glucuronidation rates of Tam, 4OHTam, Tor, and 4OHTor. Significant decreases in enzymatic activity were observed in microsomes for individuals heterozygous for −163G/A and −217T/G. These alterations in glucuronidation may lead to prolonged circulating half-lives and may potentially modify the effectiveness of these drugs in the treatment of breast cancer.